Extrahepatic approach for taping the common trunk of the middle and left hepatic veins or the left hepatic vein alone in laparoscopic hepatectomy (with videos). (8th August 2022) - Nakano, Yutaka; Abe, Yuta; Kitago, Minoru; Yagi, Hiroshi; Hasegawa, Yasushi; Hori, Shutaro; Koizumi, Wataru; Ojima, Hidenori; Imanishi, Nobuaki; Kitagawa, Yuko
Abstract: Background: Outflow control is difficult, and techniques required for effectively handling intraoperative hemorrhage during laparoscopic hepatectomy have not previously been adequately reported. Methods: Sixteen patients underwent surgery, of which 15 underwent laparoscopic left hepatectomy and one underwent laparoscopic partial hepatectomy of the caudate lobe. Encircling and taping of the common trunk of the middle (MHV) and left hepatic veins (LHV) was performed in 12 patients, and that of the LHV alone in four patients. Surgical techniques based on anatomical landmarks and histological findings are presented with videos. Histological confirmation of the anatomical landmarks for these procedures was performed in fresh cadavers to understand the anatomical structures and layers involved. Results: The median procedure duration was 15 (6‐25) minutes. All procedures were performed safely with no major bleeding. Histological findings showed fibrous connective tissue between the tunica adventitia of the inferior vena cava (IVC) and the Laennec's capsule of the liver. The layer of dissection was along the tunica adventitia of the IVC. Conclusions: The surgical techniques for encircling and taping of the common trunk of the MHV and LHV and the LHV alone based on anatomical landmarks were feasible and could allow for efficient outflow control in laparoscopic hepatectomy. Abstract : Nakano and colleagues report the method of encircling and taping the common trunk of the middle and left hepatic veins or the left hepatic vein alone in laparoscopic hepatectomy. To confirm the anatomical landmarks and the exposed layer of the procedures, the histological findings were checked in specimens from fresh cadavers.